A Global Bond: Explaining the Safe-Haven Status of US Treasury Securities - Sandy Brian Hager (European Journal of Inernational Relations, 2016)
This article offers new theoretical and empirical insights to explain the resilience of US Treasury securities as the world's premier safe or “risk-free” asset. The standard explanation of resilience emphasizes the relative safety of US Treasuries due to a shortage of safe assets in the global political economy. The analysis here goes beyond the standard explanation to highlight the importance of domestic politics in reinforcing the safe status of US Treasury securities. In particular, the research shows how a formidable “bond” of interests unites domestic and foreign owners of the public debt and works to sustain US power in global finance. Foreigners, who now own roughly half of the US public debt, have something to gain from their domestic counterparts. The top 1% of US households, which dominate domestic ownership of US Treasuries, has considerable political clout, thus alleviating foreign concerns about the creditworthiness of the US federal government. Domestic owners, in turn, benefit from the seemingly insatiable foreign appetite for US Treasury securities. In supplying the US federal government and US households with cheap credit, foreign investors in US Treasuries help to deflect challenges to the top 1% within the wealth and income hierarchy.
Keywords: 330; capital flows; global finance; global financial crisis; inequality; power; public debt